Construction Management Dissertation Abstracts: A Bounded Qualitative Meta-Study. Issue 1 (2nd January 2016) - Glick, Scott; Folkestad, James; Banning, James
ABSTRACT: A bounded qualitative meta-study framework was used to examine 61 dissertation abstracts found in the ProQuest Dissertation and Theses TM digital database from 2000 through 2014. The search terms construction management/industry and business and research were used. The overarching research question was: What can we learn from examining doctoral dissertations abstracts focusing on construction management research? The findings provide an overview of doctoral research and discussion regarding: our meta-study framework, methods and procedures, findings, and possible discussion items. The peak year for PhD awards was 2005 with 10 dissertations. Only 34% mentioned a guiding framework, and 23% used a model. Topics focused on Leadership, 33%, Management, 60%, CM Education, 5%, and Social Issues, 2%. Evidence suggests that construction education research may be relatively hidden due to the unstructured nature of the abstracts and the low number of results returned using the construction focused keywords. It is recommended that advisors and students working to complete a dissertation establish and use a structured abstract that clearly identifies among other elements the guiding framework. The use of keywords identifying Construction Management may help to increase awareness of the discipline and return more articles when construction management is used as a key search term.